Early Warning Indicators of Banking Crisis in Asian Countries - Raja HMILI (Expert Journal of Finance, 2015)
This paper aims to test the relevance of the advanced warning indicators in the prediction of systemic banking crises in 6 Asian emerging countries over the period 1973-2012. Based on multivariate panel logit model, our empirical results suggest that among 6 determinants of banking crises ranged into macroeconomic, financial and external variables, inflation demonstrates the most significant predictive power on systemic banking crises.